Virtual reality for neurorehabilitation: A bibliometric analysis of knowledge structure and theme trends - Guo, Qi-Fan; He, Lin; Su, Wei; Tan, Hui-Xin; Han, Lian-Yi; Gui, Chen-Fan; Chen, Yi; Jiang, Han-Hong; Gao, Qiang (Frontiers in Public Health, 2022)
Background: As an emerging technology, virtual reality (VR) has been broadly applied in the medical field, especially in neurorehabilitation. The growing application of VR therapy promotes an increasing amount of clinical studies. In this paper, we present a bibliometric analysis of the existing studies to reveal the current research hotspots and guide future research directions. Methods: Articles and reviews on the related topic were retrieved from the Science Citation Index Expanded of Web of Science Core Collection database. VOSviewer and Citespace software were applied to systematically analyze information about publications, countries, institutions, authors, journals, citations, and keywords from the included studies. Results: A total of 1556 papers published between 1995 and 2021 were identified. The annual number of papers increased gradually over the past three decades, with a peak publication year in 2021 (n = 276). Countries and institutions from North America and Western European were playing leading roles in publications and total citations. Current hotspots were focused on the effectiveness of VR therapy in cognitive and upper limb motor rehabilitation. The clusters of keywords contained the four targeted neurological diseases of VR, while the burst keywords represented that the latest studies were directed towards more defined types of VR therapy and greater study design. Conclusions: Our study offers information regarding to the current hotspots and emerging trends in the VR for rehabilitation field. It could guide future research and application of VR therapy in neurorehabilitation.